The important features of Macedonian capital market - Petrevska, Biljana; Simov Mishoska, Jasmina (Banja Luka College, 2020)
The objective of this paper is to analyse the important features of Macedonian capital market. This paper is going to describe the concept of Macedonian capital market and the importance of law and institutional framework in our country for the manner of operation of the market. It will consist of fourth parts. The first part of this paper will be an introduction to the framework that will explain the subject of research and that is the financial sector and the capital market as an important part of the financial sector in every economy, while the second part of the paper, focuses on the law and institutional framework of Macedonian capital market. The third part of this paper analyzes the features of Macedonian capital market from its beginning until today. Finally, in the fourth part of this paper “Conclusion”, we are giving our basic conclusions that will arise from our paper.
Keywords: financial sector, market, capital, features, capital market